Implementasi Metode Smart Dalam Menentukan Pupuk Organik Pada Perkebunan Kelapa Sawit Di PTPN IV Bah Jambi - Hafiz, Muhammad; Lubis, Ihsan; Irwan, Dedy (Journal of Computer Science and Informatics Engineering, 2024)
Organic fertilizer is fertilizer composed of living creature material, such as weathered remains of plants, animals and humans. Organic fertilizer can be in solid or liquid form and is used to improve the physical, chemical and biological properties of soil. Organic fertilizer contains more organic material than its nutrient content. Sources of organic material can be compost, green manure, manure, harvest residues (straw, stover, corn cobs, sugar cane bagasse, and coconut husks), livestock waste, industrial waste that uses agricultural materials, and municipal waste (garbage). One solution for choosing the best organic fertilizer is to use a decision support system for selecting the best organic fertilizer using the Specific, Measurable, Achievable, Relevant and Timely (SMART) method. Where the author carries out calculations using the formulas available in the SMART method. A web-based application that has been created with a decision support system can make it easier for workers to choose the best organic fertilizer. The method used, namely the SMART method, has quite accurate results by going through several calculation processes.